Discrepancy in germination behavior and physico‐chemical quality traits during wheat storage. Issue 10 (17th July 2019) - Abdullah, Muhammad; Zulkiffal, Muhammad; Din, Ahmed; Shamim, Sadaf; Javed, Anjum; Shair, Hira; Ahmed, Javed; Musa, Muhammad; Ahsan, Aneela; Kanwal, Amna
Abstract: Wheat is admired food crop that plays its role in food security in many mounting countries like Pakistan. Although harvesting time and various storage systems exert a major impact on wheat but high temperature and humidity during storage are detrimental for wheat grain health, quality, and germination knack. High storage temperature shoddily affects wheat quality. During safe wheat storage, moisture content should array from 8% to 14%. Refrigeration circumstances are imperative vehicles for the stored wheat grains to obtain utmost germination, quality, and preclusion from insect infestation. To retain better wheat quality, it should be stored below 25°C at 60% relative humidity. Some insects deteriorate wheat germination, damage the grains and cause substantial weight losses but the underlying problem may be effectively overcome with the natural fumes under hermetic conditions which also stimulates germination. Insect control in stored wheat through chemical method has residual effect and is perilous for human health. Practical applications: Wheat is the only major food crop that is cultivated in more than 60 countries of the world and 10%–20% of human daily calorie intake is fulfilled by this crop. It is very vital crop for the food security of many developing countries including Pakistan. Although wheat is mainly influenced by harvesting time and storage structures yet other factors such as moisture content, storage temperature, storage humidity, and insect infestation at storage are explained in this review which are detrimental for wheat storage stability, grain health, nutritional quality, and germination knack. Besides this, effect of storage period on grain nutritional quality under various storage facilities is described too. Furthermore, optimum keeping conditions and effective solution to minimize insect damage of stored wheat grain are described in order to ensure national food security and to avoid greater losses in gain quantity, quality, and germination ability.